Pharmacokinetic, Hemostatic, and Anticancer Properties of a Low-Anticoagulant Bovine Heparin - Santos, Roberto P.; Tovar, Ana M.F.; Oliveira, Marcos R.; Piquet, Adriana A.; Capillé, Nina V.; Oliveira, Stephan N.M.C.G.; Correia, Ana H.; Farias, José N.; Vilanova, Eduardo; Mourão, Paulo A.S. (TH Open, 2022)
Heparin is a centennial anticoagulant drug broadly employed for treatment and prophylaxis of thromboembolic conditions. Although unfractionated heparin (UFH) has already been shown to have remarkable pharmacological potential for treating a variety of diseases unrelated with thromboembolism, including cancer, atherosclerosis, inflammation, and virus infections, its high anticoagulant potency makes the doses necessary to exert non-hemostatic effects unsafe due to an elevated bleeding risk. Our group recently developed a new low-anticoagulant bovine heparin (LABH) bearing the same disaccharide building blocks of the UFH gold standard sourced from porcine mucosa (HPI) but with anticoagulant potency approximately 85% lower (approximately 25 and 180 Heparin International Units [IU]/mg). In the present work, we investigated the pharmacokinetics profile, bleeding potential, and anticancer properties of LABH administered subcutaneous into mice. LABH showed pharmacokinetics profile similar to HPI but different from the low-molecular weight heparin (LMWH) enoxaparin and diminished bleeding potential, even at high doses. Subcutaneous treatment with LABH delays the early progression of Lewis lung carcinoma, improves survival, and brings beneficial health outcomes to the mice, without the advent of adverse effects (hemorrhage/mortality) seen in the animals treated with HPI. These results demonstrate that LABH is a promising candidate for prospecting new therapeutic uses for UFH.
Keywords: unfractionated heparin; low-molecular weight heparin; pharmacokinetics; bleeding; Lewis lung carcinoma